Hyderabad, British India, and the World - Beverley, Eric Lewis, 1976- (Cambridge, United Kingdom)
xv sayfa, [2] sayfa harita, 344 sayfa
Keywords: “This examination of the formally autonomous state of Hyderabad in a global comparative framework challenges the idea of the dominant British Raj as the sole sovereign power in the late colonial period. Beverley argues that Hyderabad's position as a subordinate yet sovereign 'minor state' was not just a legal formality, but that in exercising the right to internal self-government and acting as a conduit for the regeneration of transnational Muslim intellectual and political networks, Hyderabad was indicative of the fragmentation of sovereignty between multiple political entities amidst empires. By exploring connections with the Muslim world beyond South Asia, law and policy administration along frontiers with the colonial state and urban planning in expanding Hyderabad City, Beverley presents Hyderabad as a locus for experimentation in global and regional forms of political modernity. This book recasts the political geography of late imperialism and historicises Muslim political modernity in South Asia and beyond“--